Kontribusi daya ledak otot tungkai terhadap kemampuan tendangan samping atlet pencak silat Kuciang Putiah Harimau Campo Padang Panjang - Hafid, Fathurrahman; Firdaus, Firdaus (Motion: Journal Research of Physical Education, 2023)
The problem with this research is that there are still many fighters from the Kuciang Putiah Harimau Campo College who experience defeat. The purpose of this study was to analyze the direct effects of leg muscle explosive in Pencak Silat athletes Kuciang Putiah Harimau Campo, Padang Panjang City. The method used in this study is a quantitative method using the Path Analysis technique. The population in this study were Pencak Silat athletes Kuciang Putiah Harimau Campo Padang Panjang City, totaling 61 people. In this study, the sample was determined using a purposive sampling technique, amounting to 25 people. Based on the findings and discussion, it can be concluded that there is a direct and significant effect of leg muscle explosive power on the side kick ability of the Kuciang Putiah Pencak Silat Athlete, the Harimau Campo Padang Panjang.